PRELIMINARY RESEARCH ON PAPILIO DEMOLEUS L. (LEPIDOPTERA: PAPILIONIDAE) IN DALAT - Nguyễn Thanh Thủy Tiên (Tạp chí Khoa học Đại học Đà Lạt)
Papilio demoleus L. (Lepidoptera: Papilionidae) is one of the beautiful butterflies which is usually displayed in insect collections for researching, studying and commercial purposes. This species is also one of the popular pests in citrus-producing countries throughout the world. This paper focuses on the morphological and biological characteristics of the Papilio demoleus L. in Dalat. Field-collected eggs, larva, and pupa of Papilio demoleus L. from plants belonging to Rutaceae family were reared in plastic boxes and insect cages under laboratory conditions. Larva was reared by citrus leaves. Adults were reared by 10% sugar solution. The period of egg, larvae, and pupae was 5.25±1.71 days; 31.89±3.8 days and 21.0±3.32 days, respectively. The total period of immature stages was 58.14 days. The adult longevity was 9.13±4.70 days and the fecundity was 20.67± 12.22 eggs.